Experiences of Primary School Teachers Regarding Individualized Education Programs and Mainstreaming/Integration in Türkiye - Eylem Dayı; Çetin Toraman; Pınar Özkan Renk; Belgin Öztürk (International Journal of Contemporary Educational Research)
This study addressed the experiences of primary school teachers in Türkiye regarding inclusion/integration and Individualized Education Programs (IEP). The study also addressed how mainstreaming/integration and IEPs might impact students without special needs and their parents. This qualitative study adopted a phenomenological research design. The sample consisted of 17 primary teachers recruited using criterion sampling. Data were collected using a semi-structured interview guide and analyzed using inductive content analysis and phenomenological coding. The results indicated that participants expressed the opinion that mainstreaming was not applicable in general education. They also believed that the IEP was unfunctional. They used ready-made IEPs, albeit not actively. They were of the opinion that class sizes and physical conditions of schools were not suitable for mainstreaming education and that they were left alone in the mainstreaming/integration.